2020
DOI: 10.1126/science.aba8853
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained genome targeting with near-PAMless engineered CRISPR-Cas9 variants

Abstract: Manipulation of DNA by CRISPR-Cas enzymes requires the recognition of a protospacer-adjacent motif (PAM), limiting target site recognition to a subset of sequences. To remove this constraint, we engineered variants of Streptococcus pyogenes Cas9 (SpCas9) to eliminate the NGG PAM requirement. We developed a variant named SpG that is capable of targeting an expanded set of NGN PAMs, and we further optimized this enzyme to develop a near-PAMless SpCas9 variant named SpRY (NRN and to a lesser extent NYN PAMs). SpR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
787
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(864 citation statements)
references
References 44 publications
28
787
1
2
Order By: Relevance
“…Analysis of the ClinVar database showed that over 100 of the 174 total G>A or T>C point mutations for DMD could be targeted for repair by at least one of the ABEs (iABE-NG). The recent advances in engineering Cas9 variants with non-G PAM 33,34 would further increase our targeting capacity. Moreover, the ABE editing could be designed to induce skipping of mutant exons via targeting the canonical splicing donor or acceptor 61,62 , thus further broadening the applicability of ABE editing therapy for a larger population of DMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the ClinVar database showed that over 100 of the 174 total G>A or T>C point mutations for DMD could be targeted for repair by at least one of the ABEs (iABE-NG). The recent advances in engineering Cas9 variants with non-G PAM 33,34 would further increase our targeting capacity. Moreover, the ABE editing could be designed to induce skipping of mutant exons via targeting the canonical splicing donor or acceptor 61,62 , thus further broadening the applicability of ABE editing therapy for a larger population of DMD.…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis of the ClinVar database showed that about 42.8% of the 53469 human disease-causing mutations could be potential targets for base editing correction; however, the majority (~72.4%) of these potential targets could not be suitable for SpCas9 base editing due to the lack of the 5'-NGG PAM sequence within the suitable distance from the mutations. Several variants of SpCas9 have recently been engineered with relaxed PAM (such as xCas9-3.7 30 , SpCas9-NG 31 and ScCas9 32 ) and non-G PAM 33,34 . These enzymes greatly increase the target scope for correcting human mutations.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas-based approaches for targeted genome modification have revolutionized modern biology and hold great promise for therapeutic interventions for debilitating genetic disorders. In particular, engineered enzymes have given the gene editing field an everexpanding set of tools with increased fidelity (Kleinstiver et al, 2016;Slaymaker et al, 2016), altered target specificities (Chatterjee et al, 2018;Hu et al, 2018;Nishimasu et al, 2018;Walton et al, 2020), the ability to directly introduce specific changes to a target genome (Gaudelli et al, 2017;Komor et al, 2016;Nishida et al, 2016), or improved genome modification capabilities (Aida et al, 2015;Charpentier et al, 2018;Gu et al, 2018;Jayavaradhan et al, 2019;Nakade et al, 2018;Rees et al, 2019). However, these options continue to suffer from low efficiencies, high indel rates, a narrow scope of editing outcomes, and/or a reliance upon restricted sets of suitable protospacer adjacent motifs (PAMs) in close proximity to the target site.…”
Section: Introductionmentioning
confidence: 99%
“…Our method only works at nucleotide resolution close to the sgRNA cut sites. To allow denser tiling of regions with mutations, CRISPR-nucleases with alternative or dispensable PAM requirements could be used 17,53,54 . Although indels are applicable to regulatory regions and even coding sequences [55][56][57] , point mutagenesis would enable fi ne mapping of regulatory nucleotides and amino acids.…”
Section: Discussionmentioning
confidence: 99%